La pobreza monetaria desde la perspectiva de la pobreza multidimensional: el caso peruano - Urbina Padilla, Dante Abelardo (2017)
There are several approaches to poverty, but two of them are more widely used: monetary poverty and multidimensional poverty. This paper analyzes the determinants of poverty in Peru, linking both approaches by means of a logistic regression in distinct periods. It is found that access to services (water, electricity, telephony) and housing ownership reduce remarkably the probability of being poor and that having health insurance also reduces it, but to a lesser extent. Interestingly, primary or secondary education does not have a significant impact in reducing the probability of being poor, which can be due to restrictions in the current labor market.